2015
DOI: 10.1016/j.matchar.2015.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microstructure anisotropy on room and medium temperature ECAP deformed F138 steel

Abstract: The microstructure developed during severe plastic deformation results in improved mechanical properties because of the decrease in domain sizes and accumulation of defects, mainly dislocation arrays. The characteristic deformation stages observed in low stacking fault energy (SFE) face centered cubic (FCC) materials are highly influenced by the development of the primary and secondary twinning that compete with dislocation glide. In this paper, a low SFE F138 stainless steel is deformed by equal channel angul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Probably the most widespread SPD method is the equal channel angular pressing (ECAP) and its modifications (TCAP [9], TCMAP [10], NECAP [11], etc. ), which have been proven to refine effectively the grain size to the ultra-fine-grained (UFG) scale for various materials ranging from aluminium [12], through magnesium [13], copper [14], steel [15], and also tungsten [16,17]. However, ECAP is a discontinuous process, as the majority of SPD methods including the most effective methods of high-pressure torsion (HPT) [18] are, and is only suitable for processing samples of finite dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the most widespread SPD method is the equal channel angular pressing (ECAP) and its modifications (TCAP [9], TCMAP [10], NECAP [11], etc. ), which have been proven to refine effectively the grain size to the ultra-fine-grained (UFG) scale for various materials ranging from aluminium [12], through magnesium [13], copper [14], steel [15], and also tungsten [16,17]. However, ECAP is a discontinuous process, as the majority of SPD methods including the most effective methods of high-pressure torsion (HPT) [18] are, and is only suitable for processing samples of finite dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the channel angle, ɸ and curvature angle, Ψ affected to the strain present in each passes of ECAP. Iwahashi et al [53] and Vincentis et al [54], proposed the strain accumulated, ε N during the process which can be denoted as:…”
Section: Channel Angle and Curvature Anglementioning
confidence: 99%
“…This model resolves that a higher value of channel angle will contribute to a higher strain value. In Vincentis work, the equivalent strain per pass obtained was 0.67 when 120° of die angle was used in ECAP process [54].…”
Section: Channel Angle and Curvature Anglementioning
confidence: 99%
“…Meanwhile, in FCC metals, the mechanism of grain refinement is characterized by the transformation of LAGBs to HAGBs with subsequent increase in strain [21,31]. However, grain refinement in FCC metals may also be correlated with dynamic recrystallization, which occurs in this case when high strains cause a decrease in LAGBs and an increase in HAGBs [37,38]. poles tilting slightly away from normal direction (ND) towards transversal direction (TD).…”
Section: Microstructure Evolution Of Az31 and Al 1050 Layer After Arbmentioning
confidence: 99%